ININNAWA: Pendidikan Karakter Pada Anak Dalam Tradisi Suku Bugis Di Kampung Kukup Koya Koso Kota Jayapura - Saputra, Andika Dian; Karman, Abd; Nawir, M Syukri (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
This research aimed to understand the Ininnawa tradition maintained by the Bugis people of nurturing their children in Kukup Village. The method used in this research was qualitative descriptive with a social phenomenology paradigm. Research findings: the Ininnawa tradition is a tradition where has a benefit for the Bugis generation in improving and maintaining cultural preservation to keep them facing and overcoming challenges. The Ininnawa tradition aims to increase the Bugis people's ability to adapt to their surroundings. This tradition is learning to develop intellectual skills and a principle firmly entrenched in adulthood about